ANALISA PERUBAHAN SIFAT MEKANIS BAJA AISI 1045 BERDIAMETER 25 MM AKIBAT PERLAKUAN PANAS TEMPERING DAN MENGGUNAKAN TENSILE TEST DENGAN MEDIA PENDINGIN AIR: Array - Gunawan, Rifki; Junaidi, Junaidi; Kurniawan, Fadly A. (JiTEKH, 2020)
In the process of work experienced, especially the process of selling heat received during the processing. If the cooling process is carried out slowly, it will be possible to reach each type of micro balanced according to the chemical composition and temperature of the steel. In the manufacturing process, the required chemical composition is obtained when steel is in a liquid phase at high temperatures. During the cooling process of the melting temperature, steel begins to turn into a solid phase at a temperature of 13,500 C, in this phase there is a change in micro-structure. Normalization is the process of heating the metal until it reaches the austenite phase which is then desired slowly in AC media. The cooling results are perlite and ferrite but the results are much smoother than annelling. The voltage results after the tempering process showed the highest value at 200 oC is 1482, 311 N / mm2 and the lowest value at 400 oC was 1104, 75 N / mm2.